Penetração do peróxido de hidrogênio em diferentes concentrações na câmara pulpar e o manejo da sensibilidade pós-operatória em clareamento dental - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
The objectives of this study were: 1) to evaluate the diffusion of hydrogen peroxide (HP) of bleaching gels with different concentrations from the same manufacturer, 2) quantify the HP concentration in the pulp chamber in teeth with prior application of desensitizing agents and 3) evaluate the effect of an experimental desensitizing gel on the postoperative sensitivity of patients undergoing in-office tooth bleaching. For studies 1 and 2, the quantification of HP in the pulp chamber was performed using the spectrophotometric method with the horseradish peroxidase enzyme. In study 1, 90 teeth were randomly divided into nine groups (n = 10) and submitted to different concentrations of whitening gel from the same manufacturer, simulating the home and in-office whitening procedure. In study 2, 50 teeth were selected at the different desensitizing agents: Desensibilize KF 2%, Mi Paste and Desensibilize Nano-P were applied prior to the office bleaching. In study 3, 42 patients with canines with A2 or darker color were selected and randomly divided into two groups: placebo (negative control) and treatment. Patients in the treatment group were submitted to 5% potassium nitrate and 5% glutaraldehyde gel for 10 min prior to bleaching with 35% hydrogen peroxide. The dental sensitivity was evaluated immediately, after 1 h, 24 h and 48 h of the bleaching and registered by the patients themselves through the numerical scales of 5 points and visual analog. The color was evaluated through the Vita classical, Vita Bleachedguide and Vita Easyshade spectrophotometer (Vita Zahnfabrik, Bad Sackingen, Germany), initially, 1 week after each session and one month after the end of the procedure. Data from experiments 1 and 2 were evaluated by analysis of variance (ANOVA) and tukey test for the means contrast ( = 0.05). For the analysis of the risk of dental sensitivity in study 3, the data were analyzed using the Mc Nemar test and the color change by Student's t-test ( = 0.05). It was observed that the amount of HP that reached the pulp chamber in the office bleaching group was significantly higher compared to home bleaching (p = 0.65). The home protocols presented similar results. The use of desensitizing agents prior to the office bleaching reduced the passage of HP to the pulp chamber, so that the desensitizers Mi Paste and Nano-P had lower HP concentrations in the pulp chamber (p < 0.001). It was also possible to observe that the risk of tooth sensitivity of the desensitizing gel group [31.7% (95% CI 19.6 - 46.9)] and for the control group [70.7 (95% CI 55.5 - 82.3%) were statistically significant (p < 0.0001). It can be concluded that factors such as concentration of the bleaching gel and the previous use of desensitizing agents interfere in the diffusion of PH, but the use of the experimental gel based on 5% potassium nitrate and 5% glutaraldehyde was effective in reducing post-operative in patients undergoing in-office tooth bleaching.
Keywords: Clareamento dental; Peróxido de hidrogênio; Sensibilidade da dentina; Permeabilidade do esmalte dentário; Tooth Bleaching; Hydrogen peroxide; Dentin Sensitivity; Dental Enamel Permeability; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA